Sierra Leone : Basic Agricultural Public Expenditure Diagnostic Review, 2003-2012 - World Bank (Washington, DC, 2015)
This agriculture public expenditure review (AgPER) provides key background information and guidance in this endeavor by presenting and analyzing historic data on public spending on agriculture, examining the efficiency of spending, and identifying areas where additional funds can be applied effectively to achieve national agricultural policy and comprehensive Africa agriculture development program (CAADP) objectives. The goals of the AgPER in Sierra Leone are as follows: gain a better understanding of the countrys performance in the context of the 2003 Maputo declaration; draw lessons from the past in terms of budget execution in the agricultural sector and identify bottlenecks, inefficiencies, and deviations from goals; seek and recommend corrective actions for existing and future programs with a view to improving their impact and making them more efficient and equitable; initiate the implementation of the databases and methodology required for conducting similar reviews regularly and thus contribute to the institutionalization of the process; help the government establish an environment and capabilities for results-based management, with particular emphasis on improving planning, execution, and monitoring and evaluation; and increase visibility for the government and the financial and technical partners over the sectors absorptive capacity so that the decision may be made to allocate more resources to agricultural development. This report consists of five chapters: first chapter introduces the strategic and institutional context; second chapter studies the level of public agricultural expenditure in Sierra Leone; third chapter analyzes the economic and functional composition of public agricultural expenditure (allocative efficiency); fourth chapter assesses the technical efficiency of the processes of preparation, execution, and monitoring and evaluation of agricultural budgets; and fifth chapter contains our findings and recommendations.